Fungsi Talempong Pacik Dalam Upacara Perkawinan Dan Batagak - Gea Lesmana Putra; Yurnalis Yurnalis; Syafniati Syafniati (Jurnal Musik Nusantara, 2023)
Talempong pacik is a type of percussion music that is classified as a percussion instrument (idiophone). which is made from a mixture of metal and copper or brass which is played by four or five players consisting of five or six talempongs and one gandang instrument. This talempong art is played in processions during wedding ceremonies and Batagak Pangulu ceremonies. The aim of this research is to describe the form of presentation of talempong and its function in wedding ceremonies and batagak pangulu in the lives of the people of Jorong Subarang Nagari Paninggahan, Solok Regency. This research uses a descriptive method with a qualitative approach that uses primary data through interviews and direct observations in the field and secondary data, namely data obtained through literature study in the form of books related to the art of talempong pacik. The result achieved is that the form of presentation of talempong pacik in Jorong Subarang Nagari Paninggahan, Solok Regency is that the talempong instrument is played by three players, each of whom holds two talempongs which function as the parent talempong, paningkah talempong and child talempong and one drum. The function of talempong in wedding ceremonies and batagak penghulu is as a means of ritual, entertainment, aesthetic presentation, emotional expression and means of communication.